Citronellol-functionalized natural silica: a biogenic approach for antifungal and antibacterial material applications - Lopez, Guillermo P.; Roque, Leyanet Barberia; Igal, Katerine; Espinosa, Erasmo Gámez; Bellotti, Natalia (Frontiers in Chemistry, 2025)
IntroductionNew bioactive hybrid materials to prevent biofilm-induced biodeterioration are a significant challenge in indoor environments, where contaminants from microbial films compromise structural integrity and contribute to air pollution, posing health risks from prolonged exposure to biological agents.MethodsFor the first time, diatomaceous earth or diatomite (Dt) was functionalized with quaternary ammonium salt (QAS) and a biogenic compound, citronellol, to develop a bioactive hybrid material (Dt*QC). The hybrids obtained were characterized by thermogravimetric analysis (TGA), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and Fourier-transform infrared spectroscopy (FTIR). The antifungal and antibacterial activity were assessed by agar diffusion assay, and micro/macro-dilution tests.Results and DiscussionCharacterization confirmed successful functionalization. TGA revealed organic contents of 50.9% with citronellol incorporation reaching 48.1%. SEM-EDS corroborated the incorporation of organic components. FTIR further verified the integration of functional groups while preserving the structural stability of the siliceous framework. Antimicrobial assays revealed a broader range of activity for Dt*QC. For bacterial strains, Dt*QC achieved a minimum inhibitory concentration (MIC) of 0.15 mg/mL against Staphylococcus aureus and demonstrated over 99.9% bacterial reduction, even at lower concentrations. This study highlights a novel approach to developing antimicrobial materials by functionalizing Dt with QAS and citronellol. Overall, these findings underscore the potential of Dt*QC as an advanced antimicrobial material for applications in coatings and preservation systems, offering a sustainable solution to prevent biodeterioration and microbial contamination.